2009
DOI: 10.1007/s11746-009-1523-z
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Garden Cress (Lepidium sativum L.) Seed Oil

Abstract: Garden cress (Lepidium sativum L.) is an edible, underutilised herb, grown mainly for its seeds in India. Physicochemical properties, minor components (unsaponifiable matter, tocopherols, carotenoids), fatty acid composition and storage stability of garden cress seed oil (GCO) were studied. Cold press, solvent and supercritical CO 2 extraction methods were employed to extract the oil. The total oil content of garden cress (GC) seeds was 21.54, 18.15 and 12.60% respectively by solvent, supercritical CO 2 and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
95
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(107 citation statements)
references
References 21 publications
11
95
1
Order By: Relevance
“…γ-Tocopherol content in vegetable oil is positively correlated with the amount of α-linolenic present in it [58]. These findings are consistent with those obtained by Diwakar et al, [6] who reported that γ-tocopherol is found to be the predominant tocopherol in garden cress seed oil. …”
Section: Tocopherol Contentsupporting
confidence: 88%
See 3 more Smart Citations
“…γ-Tocopherol content in vegetable oil is positively correlated with the amount of α-linolenic present in it [58]. These findings are consistent with those obtained by Diwakar et al, [6] who reported that γ-tocopherol is found to be the predominant tocopherol in garden cress seed oil. …”
Section: Tocopherol Contentsupporting
confidence: 88%
“…In the same time, the presence of erucic acid (C22:1) in garden cress seeds was not reported by Zia-Ul-Haq et al, [40]. On the other hand, the obtained fatty acid profiles for garden cress oil were similar to those reported by [6].…”
Section: Fatty Acid Composition Garden Cress Oilsupporting
confidence: 75%
See 2 more Smart Citations
“…The leaves of Lepidium are antiscorbutic, diuretic, and stimulant. The seeds are aperients, diuretic, tonic, demulcent, aphrodisiac, rubefacient, carminative, galactagogue, and emmenagogue (Nadkarni 1954;Diwakar et al 2010;Rehman et al 2012). It is supplemented in the diet of lactating women to increase the milk secretion during postnatal period (Datta et al 2011) and recommended for diarrhea and dysentery.…”
Section: Introductionmentioning
confidence: 99%